Impact of COVID-19 and containment measures on burn care: A qualitative exploratory study. Issue 6 (September 2022) - Keshri, Vikash Ranjan; Peden, Margaret; Jain, Tanu; Babu, Bontha V.; Saha, Shivangi; Singhal, Maneesh; Norton, Robyn; Jagnoor, Jagnoor
Highlights: COVID-19 and its containment measures affected the delivery of burn care in India. Change in pattern of burns and presentation to health facilities was observed. The access was limited, and the functionality of burn centres were affected. Emerging lessons are prioritization of prevention, decentralised care, and the potential of telemedicine. Abstract: Background: Burn care in India is limited by multiple constraints. The COVID-19 pandemic and the containment measures restricted access to non-COVID emergency conditions, including burns. The aim of this study was to explore the impact of the pandemic on burn care in India. Methods: Using the qualitative exploratory methods, we conducted in-depth interviews (IDI) with plastic and general surgeons representing burn units from across India. Participants were selected purposively to ensure representation and diversity and the sample size was guided by thematic saturation. Thematic analysis was undertaken adopting an inductive coding using NVivo 12 Pro. Results: 19 participants from diverse geographic locations and provider types were interviewed. Three major emerging themes were, change in patient and burn injury characteristics; health system barriers, adaptation, and challenges; and lessons and emerging recommendations for policy and practice. There was change in patient load, risk factors, and distribution of burns. The emergency services were intermittently disrupted, the routine and surgical services were rationally curtailed, follow-up and rehabilitation services were most affected. Measures like telemedicine and decentralising burn services emerged as the most important lesson. Conclusions: The ongoing pandemic has compounded the challenges for burns care in India. Urgent action is required to prioritise targeted prevention, emergency transport, decentralise service delivery, and harnessing technology for ensuring resilience in burns services.